2007
DOI: 10.1159/000112176
|View full text |Cite
|
Sign up to set email alerts
|

An <i>Apolipoprotein A-I</i> Gene Promoter Polymorphism Associated with Cognitive Decline, but Not with Alzheimer’s Disease

Abstract: Background/Aims: Accumulating biological and epidemiological evidence suggests a close link between cholesterol metabolism and the pathophysiology of Alzheimer’s disease (AD). The observation that the use of statins reduces the risk of AD sustains this hypothesis. Apolipoprotein A-I (APOA1) is the major component of the high-density lipoproteins, particles involved in reverse cholesterol transport. Therefore, genetic polymorphisms in the gene encoding APOA1 might influence cholesterol metabolism and be a risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
5
9
0
Order By: Relevance
“…All the analyses were performed using Bsurvival^, Bmeta^, Bmediate^, Betm^, Bcmprsk,^and Bmice^packages of R vers. 3.2.3 software (Buuren and Groothuis-Oudshoorn 2011;Allignol et al 2011;Team 2013;Therneau 2014;Tingley et al 2014;Gray 2014;Schwarzer 2015).…”
Section: Discussionmentioning
confidence: 99%
“…All the analyses were performed using Bsurvival^, Bmeta^, Bmediate^, Betm^, Bcmprsk,^and Bmice^packages of R vers. 3.2.3 software (Buuren and Groothuis-Oudshoorn 2011;Allignol et al 2011;Team 2013;Therneau 2014;Tingley et al 2014;Gray 2014;Schwarzer 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, two other studies report that increased levels of apoA-I/HDL may increase the risk of AD; one shows that increased HDL cholesterol levels are associated with an increasing number of amyloid plaques in human brain (50), whereas the other shows that a polymorphism in the promoter of the apoA-I gene that increases plasma apoA-I level is associated with an earlier onset of non-familial AD (20). However, a more recent study reports no association between this polymorphism and AD (21).…”
Section: Discussionmentioning
confidence: 99%
“…ApoA-I has also been shown to bind A␤ in the CSF and plasma (16 -18) and to bind fulllength APP (19). In addition, apoA-I polymorphisms have been associated with AD and/or dementia (20,21). Furthermore, epidemiological studies show a marked decrease of plasma apoA-I levels in human AD patients (22) and demonstrate that decreased HDL cholesterol and serum apoA-I concentrations are highly correlated with the severity of AD (23).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…In sharp contrast to apoE, apoAI is not synthesized in the CNS and its presence in CSF indicates transit across the blood-brain barrier (124). Polymorphisms in the gene that encodes apoAI have been correlated with AD dementia or all-cause dementia (19, 20); plasma and serum apoAI levels are decreased in patients with AD dementia (2224); and serum levels of apoAI have been associated inversely with risk of AD dementia (21). Furthermore, recent studies have shown the lack of apoAI increases cerebral amyloid angiopathy and memory deficits of AD dementia (125), and increasing plasma apoAI levels provides cognitive and neuropathological benefits in animal models of AD dementia (126).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptides do bind apoE-containing CSF lipoproteins, but not apoE itself (17, 18). Polymorphisms in the apoAI gene are associated with dementia (19, 20), and apoAI plasma or serum levels are inversely associated with AD dementia and PD (2127). ApoAI also is reported to bind Aβ in CSF and plasma.…”
Section: Introductionmentioning
confidence: 99%